Milk Transmission of HTLV-1 and the Need for Innovative Prevention Strategies - Millen, Sebastian; Thoma-Kress, Andrea K. (Frontiers in Medicine, 2022)
Breastfeeding is recommended by the World Health Organization for at least 6 months up to 2 years of age, and breast milk protects against several diseases and infections. Intriguingly, few viruses are transmitted via breastfeeding including Human T-cell leukemia virus Type 1 (HTLV-1). HTLV-1 is a highly oncogenic yet neglected retrovirus, which primarily infects CD4+ T-cells in vivo and causes incurable diseases like HTLV-1-associated inflammatory conditions or Adult T-cell leukemia/ lymphoma (ATLL) after lifelong viral persistence. Worldwide, at least 5-10 million people are HTLV-1-infected and most of them are unaware of their infection posing the risk of silent transmissions. HTLV-1 is transmitted via cell-containing body fluids such as blood products, semen, and breast milk, which constitutes the major route of mother-to-child transmission (MTCT). Risk of transmission increases with the duration of breastfeeding, however, abstinence from breastfeeding as it is recommended in some endemic countries is not an option in resource-limited settings or underrepresented areas and populations. Despite significant progress in understanding details of HTLV-1 cell-to-cell transmission, it is still not fully understood, which cells in which organs get infected via the oral route, how these cells get infected, how breast milk affects this route of infection and how to inhibit oral transmission despite breastfeeding, which is an urgent need especially in underrepresented areas of the world. Here, we review these questions and provide an outlook how future research could help to uncover prevention strategies that might ultimately allow infants to benefit from breastfeeding while reducing the risk of HTLV-1 transmission.